Preparation and properties of chlorinated epoxidised natural rubber latex and its latex-based adhesive - Thitithammawong A; Nakason C; Ruttanasupa N (Journal of Rubber Research, 2012)
Chlorinated epoxidised natural rubber (CENR) was synthesised using epoxidised natural rubber (ENR) in its latex state with an in-situ chloride ion generating substance. The influences of the molar ratios of sodium hypochlorite/sodium chloride (NaOCl/NaCl), pH and the concentration of the NaOCl/NaCl, and reaction time on the level of chlorine contents in the CENR molecules were investigated. FTIR observation showed the presence of a C-Cl band in the rubber structure upon chlorination of the ENR by mixing it with NaOCl and NaCl. The thermogravimetric analysis proved that chlorination provided the CENR with superior thermal stability than that of the ENR. The CENR latex was then formulated and compounded to prepare a latex-based adhesive. It was found that crosslink reactions generated by different vulcanisation systems caused different adhesive strengths in terms of shear strength and cleavage peel strength. Furthermore, the adhesive exhibited higher shear strength than the commercial grade adhesives (i.e. Contact and Dragon) where comparable peel strengths were obtained. However, both properties were relatively lower when compared with Diabond.
Source Year: 2012
Keywords: Chlorinated epoxidised natural rubber; Latex based adhesive; Sodium chloride; Sodium hypochlorite